Mendorong Literasi Membaca melalui Upaya Kolaboratif Pemberdayaan Perpustakaan - Calvin Girsang; Rahma Hayati (JURNAL EDUKASI NONFORMAL, 2023)
This journal discusses the importance of collaboration in enhancing reading literacy through library empowerment efforts. Library empowerment involves various programs and initiatives aimed at strengthening the role of libraries as resource and knowledge centers in society. In this context, this research explores collaborative efforts involving libraries, educational institutions, communities, and other stakeholders. The research demonstrates that collaboration in library empowerment has a positive impact on enhancing reading literacy. Through close cooperation between libraries and educational institutions, relevant resources and programs can be provided to foster reading interest and improve reading skills among children, adolescents, and adults. Additionally, involving the community in library empowerment initiatives can expand the accessibility and relevance of libraries to diverse groups within society. The findings also highlight the importance of coordination between libraries and other stakeholders such as government bodies, non-profit organizations, and local communities. By combining resources, expertise, and diverse perspectives, such collaborations can create a more holistic and sustainable reading ecosystem. This research provides insights into how collaborative efforts in library empowerment can contribute to enhancing reading literacy in society. By engaging various stakeholders, these programs can create significant and sustainable impacts in developing a strong reading culture